2012
DOI: 10.1016/j.jviscsurg.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A pseudotumoral presentation of pancreatic tuberculosis

Abstract: A 22-year-old female, with no particular past medical history except for consumption of raw milk, was hospitalized with symptoms of severe epigastric pain, penetrating to the back and associated vomiting; symptoms were progressive over a one-month period. She had no other change in her general health. Examination revealed no signs of clinical tuberculosis (sweats, weight loss, hemoptysis). Laboratory findings and tumor markers were normal.Abdominal CT revealed a heterogeneous tumoral mass in the pancreatic ist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…These features may resemble these of inflammatory or neoplastic cystic lesions of the pancreas. In a study by Nagar et al [5], CT showed hypodense collections within the pancreas associated with peripancreatic lymphadenopathy in 29 patients [32] 2007 Pancreatic abscesses and colonic perforation Nakai et al [33] 2007 Pancreatbiliary fistula Chang et al [7] 2008 Progressive dysphagia Pandita et al [14] 2009 Dyspepsia Rana et al [34] 2010 Focal pancreatitis and segmental portal hypertension Hellara et al [35] 2012 Pseudotumoral presentation while 3 patients had a complex pancreatic mass lesion. Xia et al [6] in a study on 16 patients reported that CT showed pancreatic mass with heterogenous hypodensity focus in all patients with calcification in 9 patients and peripancreatic nodules in 6 patients.…”
Section: Role Of Imaging Studiesmentioning
confidence: 99%
“…These features may resemble these of inflammatory or neoplastic cystic lesions of the pancreas. In a study by Nagar et al [5], CT showed hypodense collections within the pancreas associated with peripancreatic lymphadenopathy in 29 patients [32] 2007 Pancreatic abscesses and colonic perforation Nakai et al [33] 2007 Pancreatbiliary fistula Chang et al [7] 2008 Progressive dysphagia Pandita et al [14] 2009 Dyspepsia Rana et al [34] 2010 Focal pancreatitis and segmental portal hypertension Hellara et al [35] 2012 Pseudotumoral presentation while 3 patients had a complex pancreatic mass lesion. Xia et al [6] in a study on 16 patients reported that CT showed pancreatic mass with heterogenous hypodensity focus in all patients with calcification in 9 patients and peripancreatic nodules in 6 patients.…”
Section: Role Of Imaging Studiesmentioning
confidence: 99%
“…A spectrum of manifestations during the development of pancreatic TB is really diverse, ranging from abdominal discomfort, abdominal pain, nausea and vomiting, obstructive jaundice, loss of appetite, and weight loss to fever, night sweats, or abdominal mass [ 9 11 ]. Although there are so many symptoms for TB, patient always afflicts one or more kinds of presentations, as is demonstrated here.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon these, some neoplastic disease cannot be excluded although the patient was not old. When the pancreatic carcinoma or neoplasm occurred, the most common symptoms are turned to pain, weight loss, jaundice, and anorexia, which will become more and more serious [ 8 , 9 ]. In our case, we found that the malignancy should be highly suspected because the radiology defined exactly that a mass had low density, compressed the surrounding organs, and wrapped the blood vessels.…”
Section: Discussionmentioning
confidence: 99%